Fabrication and characterization of semiconductor based photo-catalysis for light-Driven water splitting - Abd El-Nasser, Shady (AUC Knowledge Fountain, 2018)
The straightforward, low-priced and hence extensive conversion of sun light utilizing photocatalysis in a water splitting process is the main source to provide a clean and renwable hydrogen supply. Principally, photocatalysts are semiconductor materials with a suitable band gap that can absorb incident photons to produce photogeneated charges which consequently initiate the water splitting reaction to generate oxygen and hydrogen. The process itself is typically influenced by the material properties of the semiconductor (band gap, redox potentials and crystallinity) thus, altering the band structure of the semiconductor would help build up a photocatalyst that is appropriate for susbtaintial hydrogen generation. This thesis exemplifies a detailed study of high performance yet affordable photo-electrodes for solar-driven hydrogen production using Titanium (II) oxide (TiO2). TiO2 is considered to be a favorable photocatalyst that can be used as a photoanode in the photoelectrochemical cell due to its unique properties. In particular it's high physical and chemical stability, high oxidizing power of the photogenerated holes, low-cost and non-toxicity. However, TiO2 is ideal for water splitting only under ultraviolet (UV) light due to its band gap that reaches 3.2 eV which makes its photocatalytic activity only restricted to the UV range that comprises only about 3% of the whole solar spectrum. In this study, two titania based photoanode systems were investigated in an effort to optimize the trade-off between the low external bias needed (electrical energy input) and the high photocurrent spectral response (H2 output). In the first part, Na-modified TiO2 nanostructured electrodes were studied. Varying the Na content showed a noticeable impact on the optical as well as the photoelectrochemical characteristics. The morphological characterization affirmed the presence of a discontinuous layer adsorbed over the surface of the TiO2 nanotubes where the tublar structure is kept preserved after treatment. Chemical analysis revealed no significant change in the structural properties of TiO2 upon modification which proves that the alkali ions were just dispersed within the TiO2 network. Optical properties illustrate the inclusion of conduction band tail states attributed to the disordered structure where the absorption edge is slightly shifted towards higher wavelength regions. The modified electrodes maintained nearly 81 % enhancement in the photoconductivity (0.9928 mA cm-2) in comparison with that of bare TiO2 (0.1821 mA cm-2) under AM 1.5G illumination (100 mW cm-2, 0.05 M Ba (OH) 2). Also, improved carriers' separation and mobility has been accomplished which was asserted by the electrochemical impedance spectroscopy that revealed less charge transfer resistance as well as space charge capacitance for the surface modified electrodes. Further, the Mott-Schottky analysis affirmed the observed Voc enhancement by demonstrating a negative shift in the flat band potential for all the Na+-modified electrodes with respect to that of the pristine TiO2 implying less band bending requirements. Finally, DFT calculations were implemented to add further details on the electronic structure of the disordered titania confirming the empirical findings obtained upon surface modification. In the second part of this work, hybrid PEDOT/TiO2 photoelectrodes were analyzed. The development of such nanocomposites was accomplished by controlled electrochemical anodization of Ti foil, followed by a simple and fast spin coating of PEDOT. The heterojunctions maintained superior optical sensitivity where the absorption band edge reaches nearly 694 nm with respect to that of the unsensitized (TiO2 382 nm). This clearly indicates the ability to promote water splitting under visible irradiation. Likewise, superior photoelectrochemical performance concerning the photoconductivity, and the charge transfer kinetics were recognized mainly due to the fact that the highest occupied molecular orbit (HOMO) and lowest unoccupied molecular orbit (LUMO) of PEDOT are more negative than the conduction band (CB) and the valence band (VB) of TiO2. This in return, not only narrows down the band gap but also facilitates the separation of photo-induced charges and accordingly improves the photocatalytic activity.